ANSWER
![( - \frac{3}{2} , - 1)](https://tex.z-dn.net/?f=%28%20-%20%20%5Cfrac%7B3%7D%7B2%7D%20%2C%20-%201%29)
EXPLANATION
From the graph, the coordinates of Y are:
![(3,2)](https://tex.z-dn.net/?f=%283%2C2%29)
We want to find the image of this point after a dilation by a scale factor of -½ about the origin.
The rule for the dilation is :
![(x,y)\to( - \frac{1}{2} x, - \frac{1}{2} y)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Cto%28%20-%20%5Cfrac%7B1%7D%7B2%7D%20%20x%2C%20-%20%20%5Cfrac%7B1%7D%7B2%7D%20y%29)
To find the coordinates of Y', we plug the coordinates of Y.
![Y(3,2)\to \: Y'( - \frac{1}{2} (3), - \frac{1}{2}(2) )](https://tex.z-dn.net/?f=Y%283%2C2%29%5Cto%20%5C%3A%20Y%27%28%20-%20%5Cfrac%7B1%7D%7B2%7D%20%20%283%29%2C%20-%20%20%5Cfrac%7B1%7D%7B2%7D%282%29%20%29)
![Y(3,2)\to \: Y'( - \frac{3}{2}, - 1)](https://tex.z-dn.net/?f=Y%283%2C2%29%5Cto%20%5C%3A%20Y%27%28%20-%20%5Cfrac%7B3%7D%7B2%7D%2C%20-%201%29)
The first choice is correct.
This is 1:25 (C)
Explanation:
Answer:
y = -2/3 x + 5/3
Step-by-step explanation:
y = mx + b
y = -2/3 x + b
1 = -2/3 × 1 + b
3/3 + 2/3 = b
b = 5/3
y = -2/3 x + 5/3
Answer:
.
Step-by-step explanation:
Let
and
denote the two endpoints.
The formula for the midpoint of these two points would be:
.
(Similar to taking the average of each coordinate.)
In this question, it is given that
whereas
. Substitute these two values into the expression for the coordinate of the midpoint:
-coordinate of the midpoint:
.
-coordinate of the midpoint:
.
Solve these two equations for
and
:
whereas
.
Hence, the coordinate of the other point would be
.